Zonal Reconstruction of Photonic Wavefunction via Momentum Weak Measurement. Issue 5 (3rd April 2020) - Yang, Mu; Xiao, Ya; Liao, Yu‐Wei; Liu, Zheng‐Hao; Xu, Xiao‐Ye; Xu, Jin‐Shi; Li, Chuan‐Feng; Guo, Guang‐Can
Abstract: Direct measurement of wavefunctions has attracted great interest and many different methods have been developed. However, the precision of current techniques is limited by the use of Fourier transform lenses. These measurements require to shear cut the part of particles with momentum P = 0, which greatly restricts the efficiency and application of the approaches. Here, a method to directly measure 2D photonic wavefunctions is proposed and experimentally demonstrated by combining the momentum weak measurement technology and the zonal wavefront restoration algorithm. Both the Gaussian and Laguerre–Gaussian wavefunctions are experimentally well reconstructed. This method avoids using the Fourier lens and post selection on the momentum P = 0 . This is further applied to measure wavefronts with ultra‐high spatial frequency and achieve a pixel resolution, which is difficult for traditional Shack–Hartmann wavefront sensing technologies. This work extends the ability of quantum measurement techniques and will be useful for high‐resolution wavefront sensing. Abstract : A novel method for direct photon wavefunction reconstruction is presented by combining the momentum weak value measurement technology and the classical zonal wavefront restoration algorithm. The pixel‐level resolution of the technique is demonstrated experimentally by the reconstruction of Gaussian, Laguerre–Gaussian, and even the ultra‐high spatial frequency wavefunctions. The method would be useful for high‐resolution wavefront sensing.